A protocol for an exploratory phase I mixed-methods study of enhanced integrated care for care home residents with advanced dementia: the Compassion Intervention. Issue 6 (17th June 2014) - Elliott, Margaret; Harrington, Jane; Moore, Kirsten; Davis, Sarah; Kupeli, Nuriye; Vickerstaff, Victoria; Gola, Anna; Candy, Bridget; Sampson, Elizabeth L; Jones, Louise
Abstract : Introduction: In the UK approximately 700 000 people are living with, and a third of people aged over 65 will die with, dementia. People with dementia may receive poor quality care towards the end of life. We applied a realist approach and used mixed methods to develop a complex intervention to improve care for people with advanced dementia and their family carers. Consensus on intervention content was achieved using the RAND UCLA appropriateness method and mapped to sociological theories of process and impact. Core components are: (1) facilitation of integrated care, (2) education, training and support, (3) investment from commissioners and care providers. We present the protocol for an exploratory phase I study to implement components 1 and 2 in order to understand how the intervention operates in practice and to assess feasibility and acceptability. Methods and analysis: An 'Interdisciplinary Care Leader (ICL)' will work within two care homes, alongside staff and associated professionals to facilitate service integration, encourage structured needs assessment, develop the use of personal and advance care plans and support staff training. We will use qualitative and quantitative methods to collect data for a range of outcome and process measures to detect effects on individual residents, family carers, care home staff, the intervention team, the interdisciplinary team and wider systems. Analysis will include descriptive statistics summarising process and care home level data, individual demographic and clinical characteristics and data on symptom burden, clinical events and quality of care. Qualitative data will be explored using thematic analysis. Findings will inform a future phase II trial. Ethics and dissemination: Ethical approval was granted (REC reference 14/LO/0370). We shall publish findings at conferences, in peer-reviewed journals, on the Marie Curie Cancer Care website and prepare reports for dissemination by organisations involved with end-of-life care and dementia.